2014
DOI: 10.1155/2014/320930
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency Is Associated with Lower Physical Function in Patients with Heart Failure and Diabetes

Abstract: Vitamin D deficiency is frequent among patients with heart failure (HF) and diabetes, disorders associated with exercise intolerance and muscle weakness. This study aims to search for associations between vitamin D sufficiency and physical function indexes in patients with HF and diabetes. A cross-sectional study of 146 HF patients, 39.7% with diabetes, at a Brazilian tertiary outpatient clinic was performed. Patients underwent clinical evaluation, 6-minute walk test (6 MWT), handgrip strength, physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
9
1
Order By: Relevance
“…The percentage of our patients who had an optimal 25(OH)D concentration was 41.5% in comparison to only 8.8% in a study on the population of Israel [ 20 ], 25% in a Dutch study [ 11 ], and 29.5% in a Brazilian population study [ 21 ]. In the Israeli study, some patients with normal 25(OH)D concentration had previously received vitamin D supplementation [ 20 ].…”
Section: Discussioncontrasting
confidence: 56%
“…The percentage of our patients who had an optimal 25(OH)D concentration was 41.5% in comparison to only 8.8% in a study on the population of Israel [ 20 ], 25% in a Dutch study [ 11 ], and 29.5% in a Brazilian population study [ 21 ]. In the Israeli study, some patients with normal 25(OH)D concentration had previously received vitamin D supplementation [ 20 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Low levels of vitamin D are associated with a decrease in muscle strength , and vitamin D supplementation has been shown to improve muscle strength and gait, with a reduction in falls . Severe vitamin D deficiency can lead to a reduction in proximal muscle strength and size as well as increased IMNCT . Several randomized studies have recently shown significant improvements in both muscle volume and strength after treatment with vitamin D .…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental and clinical studies have demonstrated that, besides its well-known effects on calcium homeostasis and bone metabolism, vitamin D has many other important functions [1,2]. Accumulating evidence has implicated vitamin D deficiency as a risk factor for several diseases [1][2][3][4][5][6]. Low level of vitamin D is proposed to be associated with insulin resistance and insulin secretion derangements resulting in the development of T2DM [7].…”
Section: Introductionmentioning
confidence: 99%